System and method for protecting digital documents and preventing unauthorized distribution of documents to third party - Wan Adnan, Wan Azizun; Ramli, Abdul Rahman; Syed Abdul Rahman, Sharifah Mumtazah; Samsudin, Khairumizan; Al-Maweri, Nasr Addin Ahmed Salem (2013)
A method for protecting digital document from unauthorized distribution of the document to any third party includes the steps of receiving the at least one digital document by at least one client, dynamically generating watermarking bits to be embedded on to said at least one digital document, embedding the watermarking bits on to the digital document, and generating at least one watermarked digital document.